PREFERENSI CALON PEMIMPIN DI PEMILIHAN UMUM TAHUN 2024 DALAM PEMBERITAAN MEDIA ONLINE - Larasati, Yuniar Galuh; Fernando, Henky (Interaksi: Jurnal Ilmu Komunikasi, 2023)
Preferences for 2024 leaders can be seen from the electability of leaders in the 2019 general election. This preference indicates that the prospective leaders who will emerge in the 2024 general election are a continuation of political activity in 2019. This study aims to explain the preferences of prospective leaders in the 2024 general election. Because so far there are still few studies that pay special attention to the preferences of prospective leaders in the context of futuristic elections. This research is descriptive qualitative in nature. Data collection was conducted through a process of reading 1,000 online news articles using the search keywords "2019 and 2024 general elections in Indonesia" on the Google search engine. The analysis in this study was conducted by reducing, describing, and interpreting the data thematically inductively. The findings in this study show that the preferences of prospective leaders in the 2024 general election are not much different in terms of profession or social status. This study also recommends the importance of research that analyzes the preferences of prospective leaders in the 2024 elections with a more empirical approach.